(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article examines the theoretical, technological, and practical aspects of integrating generative artificial intelligence ( GenAI ) into personalized educational platforms. Based on an analysis of current research on intelligent learning systems and large-scale language models, the potential of generative technologies for improving learning effectiveness through adaptive delivery of materials, automatic content generation, personalized feedback, and support for metacognitive strategies is assessed.